2008
DOI: 10.1080/02643290701862316
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of an inhibition deficit for word production and comprehension: Evidence from the semantic blocking paradigm

Abstract: We investigated the semantic blocking effect in picture naming and word-picture matching for two nonfluent aphasic patients who show evidence of a deficit in inhibiting verbal representations (M.L. and B.Q), one fluent aphasic patient (K.V.), and neurologically intact control participants. In two picture-naming tasks (Experiments 1A and 1B), M.L. and B.Q, relative to controls, showed a greatly exaggerated semantic blocking effect in naming latencies that increased dramatically across repeated presentations. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 37 publications
5
109
3
1
Order By: Relevance
“…Instead, selective inhibition is also recruited when several responses are highly coactivated because they are part of a small response set or have recently been produced (as in semantic blocking). Though the current study is, to our knowledge, the first to demonstrate directly that selective inhibition can be involved in the absence of overt distractor stimuli that induce different degrees of conflict, the result fits in well with the observation of Biegler, Crowther, and Martin (2008) that patients with a deficit in inhibiting verbal representations showed a greatly exaggerated semantic blocking effect.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, selective inhibition is also recruited when several responses are highly coactivated because they are part of a small response set or have recently been produced (as in semantic blocking). Though the current study is, to our knowledge, the first to demonstrate directly that selective inhibition can be involved in the absence of overt distractor stimuli that induce different degrees of conflict, the result fits in well with the observation of Biegler, Crowther, and Martin (2008) that patients with a deficit in inhibiting verbal representations showed a greatly exaggerated semantic blocking effect.…”
Section: Discussionsupporting
confidence: 89%
“…En términos generales, los hallazgos de la presente investigación resultan consistentes con los de estudios previos en los que se halló evidencia acerca del efecto facilitador de la EdA temprana sobre la producción léxica en pacientes afásicos (Biegler et al, 2008;Brown & Watson, 1987;Carroll & White, 1973;Morrison et al, 1992). Es plausible, entonces, considerar que la recuperación de representaciones fonológicas constituye un punto crítico en el proceso y donde la condición de afasia produce un mayor efecto adverso.…”
Section: Discussionunclassified
“…Past investigations have shown that individuals with aphasia, in addition to linguistic deficits, demonstrate some signs of IC impairments (13,22,23). In this regard, models of word production suggest successful lexical retrieval is dependent on the ability to limit interference from co-activated lexical-semantic representations (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the continuous need to inhibit these competitors results in a delay in word retrieval. Furthermore, during the congruent condition of the paradigm, non-fluent PWAs have shown higher SIE relative to neurologically healthy patients (13,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation